Uruguay : Selected Issues. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2020)
This Selected Issues paper studies economic growth in Uruguay. Following the 2002 crisis, Uruguay had a remarkable economic recovery. The major growth acceleration in 2004-14 was explained by a combination of positive external factors, recovery from crisis, and emergence of new export sectors. With external factors no longer a support for growth, Uruguay needs to leverage its strengths to raise growth sustainably. Uruguay's high level of institutional quality and social cohesion provides a stable container for growth. A comparison relative to its trading partners and high growth peers helps identify areas that Uruguay can further enhance to unleash its growth potential. These include, a strong, flexible, and equitable labor market, better education outcomes, higher private sector dynamism, and continued macro stability. Structural policy reforms on key constraints to the private sector will help realize the potential of the new export industries and set the stage for inclusive growth. A strong and credible macro policy framework is also essential for growth sustainability. Efforts to reduce debt, inflation, and dollarization and keep them at low levels will lay the foundations for structural reforms to flourish.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet